Teacher education library e-resources integration assessment - Alois Matorevhu (Association for Scientific Computing Electrical and Engineering(ASCEE), 2021)
Expensive technological hardware and software, prohibitively high cost of installing e-learning systems, the dedication required in terms of time and skills development, and experts required to service e-learning resources systems are some challenges developing countries face in using e-resources for teaching and learning. In the context of these challenges, this study was conducted at a library of a secondary teachers’ college Y in Zimbabwe to gain insight into the nature of E-Resources Integration. Qualitative research methods involving interviews, observations, and document analysis were used to generate data. Interviewees who volunteered were pre-services teachers, teacher educators, Librarians, and ICT personnel managing the e-resources system. Through thematic analysis, data were presented as verbatim, and narratives were interpreted to unpack meaning imbued. Findings show that power outages, poor internet connectivity, lack of e-resources awareness by prospective users, competencies in using e-resources, and computers, were factors that inhibited effective e-resources use for teaching and learning. As a recommendation, libraries should design and provide e-learning resource services that motivate learners consistent with their information needs, increasing the probability of using such resources.